Pro-survival role of protein kinase C epsilon in Philadelphia chromosome positive acute leukemia. Issue 2 (1st February 2016) - Loi, To Ha; Dai, Pei; Carlin, Stephen; Melo, Junia V.; Ma, David D. F.
Abstract : Durable responses to imatinib monotherapy are rarely seen in aggressive forms of Philadelphia chromosome positive (Ph+) leukemias. To investigate the possible cause of treatment failure we examined the role of protein kinase C epsilon (PKCE), an oncogene highly implicated in the development of solid tumors and resistance to chemotherapy. We found high levels of PKCE transcripts in Ph+ acute lymphoblastic leukemia (ALL) cells from patients and cell lines, and imatinib resistant chronic myeloid leukemia, which were also less responsive to imatinib-induced apoptosis than Ph+ cells with lower PKCE expression. Furthermore, the siRNA-mediated knockdown or peptide inhibition of PKCE in Ph+ cells increased imatinib-induced apoptosis while overexpression of PKCE reduced imatinib-induced apoptosis, with concomitant increase in the pro-survival factor AKT. Our results suggest PKCE plays a protective role against apoptosis induced by BCR-ABL inhibition in Ph+ leukemias with high PKCE expression, such as Ph+ ALL.